Management of traumatic liver injuries, Mafraq hospital experience, UAE - Alkatary, Mohammed M.; Miller, Jody R.; Turekeyev, Bakhyt; Al Ayoubi, Fawzi (International Surgery Journal, 2017)
Background: The purpose of this retrospective study is to evaluate our institutional practice on the management of traumatic liver injuries and evaluate the main causes of failure of non-operative management (NOM). Methods: This is a retrospective study done in Mafraq Hospital, Abu Dhabi, UAE, during the period between January 2014 and January 2016. The patients were reviewed with regards of the grade of liver injuries, blood transfusion, imaging done, surgical intensive care unit (SICU) admission and serial vital signs and hemoglobin level. Also, we included the patient who required emergency laparotomy and damage control surgery. Focused assessment by ultrasound for trauma (FAST) was done in all liver trauma patients upon arrival to ED along with arterial blood gases, chest and pelvic X-rays. Computed tomography (CT) scans with angiography was done in all responder and stable patients. In transient responder patient CT was done on the window period of responding to resuscitation. Non-responder patients were taken immediately for exploration laparotomy, which include either control of bleeding or perihepatic packing. Results: This study included 75 patients admitted to our facility with different grades of liver injuries. 36 (48%) patients were admitted with grade I, II liver injuries which represent most of our admissions. 27 (36%) patients were admitted with grade III, 10 (13.33%) patients with grade IV while the least number was with grade V (2 patient, 2.66%). Non-operative management (NOM) or conservative treatment was successful in 34 patients admitted with grade I, II liver injuries whereas other 2 patients were explored for associated mesenteric and splenic injuries. On the patients admitted wit grade III liver injuries NOM was successful on 22 patients. The results of management of grade IV injuries showed that NOM was successful on 5 patients while the patients with grade V were managed operatively due to instability. Conclusions: Management of traumatic liver injuries is a multidisciplinary team work requiring trauma surgeon, interventional radiology, intensive care unit beside facility for trauma CT and massive blood transfusion. Management of traumatic liver injuries is depending on hemodynamic status of the patient and not the grade of injury.